L’Islam e le immagini. La potenza sinestetica della Parola - Tomasello, Dario (Scenari, 2021)
Exploring, in a diachronic way, the problem of images in the Islamic tradition, means facing a crucial and complex knot that directly calls into question the notion of representation destined to hold together the question of the gaze and the possibility of its effective realization. In this sense, the first misunderstanding that is to be found concerns the idea that Islam, beyond the prohibition of images linked to places and moments of worship, has completely censored the use of images, banning them from its own tradition and therefore excluding any type of visual culture that concerns it or, according to some scholars’ opinion, producing an iconoclastic culture.